A DIACHRONIC ANALYSIS OF THE CONCEPT “MONEY” - Y. S. Denisenkova (Vestnik MGIMO-Universiteta)
The article provides a diachronic analysis of the concept “money” in the Russian and English linguacultures. The author studies the genesis and development of money in Russia and Great Britain, and conducts a research on the formation of “money” terminology in the corresponding languages. As part of the study it has been found out that the historical development of the concept “money” in the Russian and English linguacultures has a number of common features: the cores of the concepts, the lexical items «деньги» and “money”are borrowings that entered the vocabularies of the corresponding languages at the same time; the usage of foreign monetary units, in the first place, Byzantine coins, before the introduction of national currencies, influenced “money” terminology, breeding numerous words of foreign origin, as well as the design of money. The article also outlines the etymology of basic monetary units, such as the grzywna, the kuna, the denga, the ruble, the polushka, the kopeck, the altyn ,the chervonets – in Russian, the sterling, the pound, the penny, the shilling, the farthing, the unit, the noble, the sovereign – in English. The author finds a correlation between peculiarities of money development and the evolution of money nomenclature in Russian and English. The concluding section presents similar features and common laws of the concept “money” in the two linguacultures.